0
$\begingroup$

Compute $$\large\lim_{n\to \infty}\left(\left(\prod_{i=1}^{n+1}{i^{i^p}}\right)^{1/(n+1)^{p+1}} - \left(\prod_{i=1}^{n}{i^{i^p}}\right)^{1/n^{p+1}}\right),$$ where $p$ is some nonnegative real number. I found this problem while working through the Problems in Real Analysis: Advanced Calculus on the Real Axis by Teodora-Liliana Radulescu, Titu Andreescu, and Vicenţiu D. Rădulescu, but I don't know how to do it. Can someone help me?

$\endgroup$
  • 1
    $\begingroup$ Not sure if this helps, but note that this can also be expressed as $\left(e^{\text{HurwitzZeta}^{(1,0)}(-p,n+2)-\zeta '(-p)}\right)^{(n+1)^{-p-1}}-\left(e^{\text{HurwitzZeta}^{(1,0)}(-p,n+1)-\zeta '(-p)}\right)^{n^{-p-1}}$ $\endgroup$ – Joseph Eck May 21 '18 at 21:46
  • 1
    $\begingroup$ I don't think that was the intent of the problem since the Hurwitz-Zeta function wasn't even part of the text. Though, it may help that $$\lim_{n\to\infty}\frac{\left(\prod_{i=1}^n{i^{i^p}}\right)^{1/n^{(p+1)}}}{n^{1/(p+1)}} = e^{-1/(p+1)^2}.$$ $\endgroup$ – Anon May 21 '18 at 21:56
3
$\begingroup$

The calculations got a bit messy so there could be errors, let me know if you find some.

Let the sequence $a_n$ be defined by $a_n = \prod\limits_{i=1}^n i^{i^p}$.

Then by Abel's summation formula we have $$\log \left(a_n^{1/n^{p+1}}\right) = \frac{1}{n^{p+1}}\sum\limits_{i=1}^ni^p\log i = \frac{1}{n^{p+1}}\left(n^pS(n) - p\int\limits_1^nx^{p-1}S(x) \text{d}x\right)$$

where $S(x) = \sum\limits_{1 \leq i \leq x}\log i = x \log x - x + \mathcal{O}\left(\log x\right)$.

The expression becomes messy: $$\log n - 1 + \mathcal{O}\left(\frac{\log n}{n}\right) - \frac{p}{n^{p+1}}\int\limits_1^nx^p\left(\log x - 1 + \mathcal{O}\left(\frac{\log x}{x} \right)\right)\text{d}x = $$

$$\log n - 1 + \mathcal{O}\left(\frac{\log n}{n}\right) - \frac{p}{n^{p+1}}\int\limits_1^nx^p\left(\log x - 1\right)\text{d}x + \mathcal{O}\left(\frac{p}{n^{p+1}}\int\limits_1^nx^{p-1}\log x \text{d}x\right) = $$

$$\log n - 1 + \mathcal{O}\left(\frac{\log n}{n}\right) - \frac{p}{n^{p+1}}\left(\frac{n^{p+1}\left((p+1)\log n - 1\right)+1}{(p+1)^2} - \frac{n^{p+1}-1}{p+1}\right) + \mathcal{O}\left(\frac{\log n}{n}\right) = $$

$$\log n - 1 + \mathcal{O}\left(\frac{\log n}{n}\right) -\frac{p}{p+1}\log n + \frac{p}{(p+1)^2} + \frac{p}{p+1} + \mathcal{O}\left(\frac{\log n}{n}\right) = $$

$$\frac{\log n}{p+1}-\frac{1}{(p+1)^2}+\mathcal{O}\left(\frac{\log n}{n}\right)$$

So we get $$a_n^{1/n^{p+1}} = \left(1+\mathcal{O}\left(\frac{\log n}{n}\right)\right)e^{-1/(p+1)^2}n^{1/(p+1)}$$

Then we have $$a_{n+1}^{1/(n+1)^{p+1}} - a_n^{1/n^{p+1}} = e^{-1/(p+1)^2}\left((n+1)^{1/(p+1)}-n^{1/(p+1)}\right) + \mathcal{O}\left(n^{-p/(p+1)}\log n\right)$$

So we finally get $$a_{n+1}^{1/(n+1)^{p+1}} - a_n^{1/n^{p+1}} = \mathcal{O}\left(n^{-p/(p+1)}\log n\right)$$

which converges to $0$.


I just realized that the last statement holds only for $p \gt 0$. If $p = 0$, the bound is not strong enough, and we need a better approximation.

When $p = 0$, the formula for $\log\left(a_n^{1/n^{p+1}}\right)$ becomes: $$\log\left(a_n^{1/n^{p+1}}\right) = \frac{1}{n}\sum\limits_{i=1}^n\log i = \frac{1}{n}S(n)$$

and we use the better estimate $$S(n) = \sum\limits_{i=1}^n\log i = n\log n - n + \frac{1}{2}\log n + C + \mathcal{O}\left(\frac{1}{n}\right)$$ coming from Euler-Maclaurin summation (the constant value is $C = \log\sqrt{2\pi}$ but this is not necessary here).

Then we get $$\log\left(a_n^{1/n^{p+1}}\right) = \log n - 1 + \frac{1}{2}\frac{\log n}{n} + \frac{C}{n} + \mathcal{O}\left(\frac{1}{n^2}\right)$$

and so $$a_n^{1/n^{p+1}} = \frac{n}{e}\left(1 + \frac{\log n}{2n} + \mathcal{O}\left(\frac{\log^2 n}{n^2}\right)\right)\left(1 + \frac{C}{n} + \mathcal{O}\left(\frac{1}{n^2}\right)\right)\left(1 + \mathcal{O}\left(\frac{1}{n^2}\right)\right)$$ $$a_n^{1/n^{p+1}} = \frac{1}{e}\left(n + \frac{1}{2}\log n + C\right) + \mathcal{O}\left(\frac{\log^2 n}{n}\right)$$

Then we have $$a_{n+1}^{1/(n+1)^{p+1}} - a_n^{1/n^{p+1}} = \frac{1}{e}\left(1 + \frac{1}{2}\log\left(1+\frac{1}{n}\right)\right) + \mathcal{O}\left(\frac{\log^2 n}{n}\right)$$ $$a_{n+1}^{1/(n+1)^{p+1}} - a_n^{1/n^{p+1}} = \frac{1}{e} + \mathcal{O}\left(\frac{\log^2 n}{n}\right)$$

so the limit is $\frac{1}{e}$ in the case where $p = 0$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.